Does coadministration of transforaminal epidural steroid injection with sedation improve patient satisfaction? a prospective randomized clinical study - (:unkn) unknown (American Society of Interventional Pain Physicians, 2019)
Background: Transforaminal epidural steroid injection (TFESI) can be administered with or without sedation in clinical practice. Objectives: The aim of this study was to compare both procedures in terms of patient and physician satisfaction, preoperative anxiety level, procedural pain level, and complications. Study Design: A prospective randomized trial. Setting: A university hospital interventional pain management center. Methods: The study included patients scheduled for single-level unilateral TFESI. The patients were randomized into 2 groups. The first group underwent TFESI without sedation, whereas the second group underwent TFESI with sedation. The Likert scale was used to determine the patient and physician satisfaction, and the Numeric Rating Scale (NRS-11) was used to determine the procedural pain level. Cases in which the procedure was to be repeated, the patient was questioned if they desired to undergo the procedure with the same technique. Results: A total of 64 patients, (31 [48.4%] in the sedation group) were included. In the sedation group, the patient and physician satisfaction were significantly higher (P = 0.0001), the periprocedural NRS-11 scores were significantly lower (P = 0.0001), and the rate of desire to have the intervention with the same technique was higher (P = 0.001). After the regression analysis, we reported that there was a significant correlation between being in the sedation group and NRS-11 procedure scores, the desire to have the same technique, and patient and physician satisfaction (odds ratio [OR], 0.341; OR, 0.648; OR, 0.329; OR, 0.514; P = 0.0001). Limitations: Both patients and physicians were unblinded. Conclusions: Coadministration of TFESI with sedation improves patient and physician satisfaction. Additionally, the low periprocedural pain level results in patients’ demand for the intervention to be performed with sedation in the event of repetition of the procedure. © 2019 Pain Physician. All rights reserved.
Keywords: Patient satisfaction; physician satisfaction; sedation; transforaminal epidural steroid injection